Pregnancy Outcomes in Pregnant Women with Symptoms of Covid-19 Admitted to Ayatollah Mousavi Hospital in Zanjan in 2019-2020 - Parvin Mohebbi; Azam Maleki; Mahsa Piri (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Following the spread of Covid-19 worldwide and the increase in the percentage of pregnant women suffering from the disease, it will be very important to investigate its consequences in pregnancy. Objectives: The present study was conducted to determine pregnancy outcomes in pregnant women with symptoms of covid-19 admitted to Ayatollah Mousavi Hospital in Zanjan in 2019-2020. Methods: In this study, the pregnancy outcomes in 89 pregnant women with symptoms of covid-19 admitted to Ayatollah Mousavi Hospital in Zanjan were investigated with document review and file reading. The sampling method was complete enumeration. Maternal and neonatal outcomes were collected using a checklist and analyzed with descriptive statistics in SPSS version 22 Software. Results: The most common symptoms in hospitalized pregnant women were cough (51.7%) and dyspnea (40.4%). In the laboratory results of pregnant women, leukocytosis, fasting hyperglycemia, increased CRP and alkaline phosphatase were evident. In terms of maternal outcomes, 27% of women had more than one of the examined outcomes. 13.5% had gestational diabetes and 11.2% of mothers had a premature delivery. Regarding neonatal outcomes, fetal heart rate disorder, hospitalization in the neonatal intensive care unit (37.5%), and the need for resuscitation in the first minute (28.1%) were the most reported outcomes. Conclusion: Considering the increase in adverse maternal and neonatal outcomes in pregnant women with symptoms of covid-19, it is suggested to plan for access to special care to improve the outcomes and implement awareness programs to prevent pregnant mothers from this infection.